Menu Close

dx-1-x-2-




Question Number 92138 by hore last updated on 05/May/20
∫(dx/(1+x^2 ))
dx1+x2
Answered by john santu last updated on 05/May/20
tan^(−1) (x) + c
tan1(x)+c
Answered by Rio Michael last updated on 07/May/20
∫ (dx/(1 + x^2 ))  let x = tan θ ⇒ (dx/dθ) = sec^2 θ  ⇒ ∫(dx/(1+x^2 )) = ∫ (1/(1+ tan^2 θ))  sec^2 θ dθ                       = ∫((sec^2 θ)/(sec^2 θ))dθ                 _(1 + tan^2 θ = sec^2 θ)                       = ∫ dθ = θ + C  but x = tan θ ⇒ θ = tan^(−1) x  ⇒∫ (dx/(1 + x^2 )) = tan^(−1) x + C
dx1+x2letx=tanθdxdθ=sec2θdx1+x2=11+tan2θsec2θdθ=sec2θsec2θdθ1+tan2θ=sec2θ=dθ=θ+Cbutx=tanθθ=tan1xdx1+x2=tan1x+C

Leave a Reply

Your email address will not be published. Required fields are marked *